A comparison of EISCAT and Dynasonde measurements of the auroral ionosphere - K. J. F. Sedgemore; P. J. S. Williams; G. O. L. Jones; J. W. Wright (Annales Geophysicae, 1996)
Incoherent-scatter radar and ionospheric sounding are powerful and complementary techniques in the study of the Earth's ionosphere. The work presented here involves the use of the Tromsø Dynasonde as a correlative diagnostic with the EISCAT incoherent-scatter radar. A comparison of electron-density profiles shows how a Dynasonde can be used to calibrate an incoherent-scatter radar and to monitor changes in the system. Skymaps of the direction of Dynasonde echoes are compared with EISCAT-derived density profiles to illustrate how a Dynasonde can be used to measure the drift velocity of auroral features. Vector velocities fitted to Dynasonde echoes are compared with EISCAT-derived plasma velocities. The results show good agreement when the data are taken during quiet to moderately active conditions and averaged over time scales of 30 min or more.